2019
DOI: 10.3389/fneur.2019.01003
|View full text |Cite
|
Sign up to set email alerts
|

Stress Hyperglycemia and Outcome of Non-diabetic Patients After Acute Ischemic Stroke

Abstract: Background and Purpose: Stress hyperglycemia is relative hyperglycemia after suffering an acute illness such as stroke, even without preexisting diabetes. Our study aimed to determine the relationship between stress hyperglycemia and outcome of non-diabetic patients with acute ischemic stroke.Methods: Data were derived from the ACROSS-China (Abnormal Glucose Regulation in Patients with Acute Stroke across China) registry. Patients with ischemic stroke but without a history of diabetes mellitus were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 26 publications
(39 reference statements)
3
48
0
2
Order By: Relevance
“…Previous study showed that such relative measures controlling for background glycemia better predicted prognosis of critical illness than absolute hyperglycemia ( 6 8 ). We previously found that glucose/HbA1c ratio was related to all-cause death in people with acute ischemic stroke ( 9 ). In the current study, we further added evidence that glucose/HbA1c ratio could predict neurological deficit, in addition to mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study showed that such relative measures controlling for background glycemia better predicted prognosis of critical illness than absolute hyperglycemia ( 6 8 ). We previously found that glucose/HbA1c ratio was related to all-cause death in people with acute ischemic stroke ( 9 ). In the current study, we further added evidence that glucose/HbA1c ratio could predict neurological deficit, in addition to mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that relative hyperglycemia, defined as glucose/HbA1c ratio or admission glucose divided by estimated average glucose derived from HbA1c, might be a more reliable method to measure the degree of stress hyperglycemia and a better predictor for outcomes of acute illness than absolute hyperglycemia ( 6 8 ). Our recent study showed that relative hyperglycemia of glucose/HbA1c ratio was related to mortality in the ischemic stroke people without diabetes ( 9 ). However, its association with neurological functional disability is still undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies [ 30 , 31 , 32 ], we adopted the following definitions of vascular risk factors: (1) previous transient ischemic attack/stroke was defined if the patient had a history of ischemic (transient attack or stroke) or hemorrhagic cerebrovascular disease; (2) the presence of cardiovascular disease was based on the history of previous ischemic heart disease and/or revascularization treatment using percutaneous coronary intervention/coronary artery bypass grafting; (3) atrial fibrillation was defined if the patient had past medical history of atrial fibrillation that had been confirmed in medical records; (4) high blood pressure was defined as the history of hypertension and/or use of antihypertensive medication; (5) a history of diabetes mellitus that had been confirmed in medical records and/or use of insulin/oral hypoglycemic agents were considered for defining diabetes; (6) a presence of hypercholesterolemia was based on the use of lipid-lowering medications; (7) information on active tobacco use was used for defining patient as a current smoker.…”
Section: Methodsmentioning
confidence: 99%
“…Ischemic stroke is identified as one of the major causes of disability and mortality worldwide. Hyperglycemia is an important independent risk factor for ischemic stroke and induces the occurrence and development of cerebral I/R damage [ 1 , 2 ]. Previous studies have shown that the exacerbation of ROS production, promotion of neuroinflammation, and extensive programmed cell death are possible mechanisms associated with hyperglycemia-exacerbated cerebral I/R damage.…”
Section: Introductionmentioning
confidence: 99%